A Thermal Analysis of the Internal Flow in 2 Helical Coils for the Delignification Process of Sugar Cane Bagasse Using Superheated Steam - Loayza, Juan Carlos (2022)
The present work proposes an analysis of the internal temperature flow in two types of helical coils, whose number of turns is 6 and 10, for the sugar cane bagasse delignification process, using superheated steam as a heat source. The analysis seeks to find the ideal number of turns for the process, the inlet pressure, and the temperature range in which the coil should operate to provide the working temperature for the reaction. This proposal will be carried out using Ansys fluent version 19.2 educational simulation software, where the coils were designed and the temperature and pressure parameters of the superheated steam flow to travel through the internal part of the helical coil were introduced. As a result, with a number of coils of 10 and an inlet pressure of 0.4 MPa, an efficiency of 96.545% was achieved to maintain the temperature along the coil path. This allows its application for bagasse delignification.